Role of Apparatus Competence, Organizational Commitment, Community Participation, Technology Use, and Transparency in Fund Management - Santi Suciningtyas; Suripto Suripto (Indonesian Journal of Multidisciplinary Science, 2021)
The central government's efforts to accelerate village progress throughout Indonesia are evidenced by the distribution of the budget for village funds throughout Indonesia. So that village fund management accountability is an important thing to research, because it will have an impact on the achievement of development program plans.The purpose of this study was to determine and analyze the role of apparatus competence, organizational commitment, community participation, utilization of information technology and transparency, against decision village fund management. The population in this study were 247 village officials with a sample of 25% of the sample as many as 65 people. Analysis of the data in this study is Instrumental Test (Validity and Reliability), Classical Assumption Test, Regression Analysis and Hypothesis Testing is to use t test and F test. From the partial test results:partial hypothesis testing used t-test, obtained the value of tcount for variable Apparatus Competence (X1) of 2.687, tcount for the variable Organizational Commitment (X2) of 2.411, tcount for the variable Society participation (X3) of 2,620, tcount forthe variable Utilization of Information Technology (X4) of 2.181, tcount for the variable transparency (X5) of 2,552, with the ttable of 1,998 criteria used in this test. From these results it is known that all variables have a positive and significant effect on village fund management accountability. Furthermore, to test the significance of the multiple linear regression coefficient as a whole, the F test was used and obtained F count of 8,520 which means that village fund management accountability are jointly influenced apparatus competence, organizational commitment, community participation, utilization of information technology and transparency.